Local Area Estimates and Geographical Patterns of Australia’s Sexual Minority Population - Wilson, Thomas; Temple, Jeromey (My University, 2021)
The need for subnational population statistics by sexual identity is being increasingly recognised for a variety of service delivery, analysis, and policy purposes. However, such statistics are rarely produced by statistical offices or researchers. The aims of the paper are to describe a new method for calculating subnational estimates of the population aged 18 and over by sexual identity, and apply it to produce mid-2016 estimates for local areas in Australia. Census counts of persons in same-sex and opposite-sex relationships, survey data by sexual identity and partnership status, and official Estimated Resident Population data are used. The method first involved preparing census-like counts of populations by sexual identity, and then scaling them using iterative proportional fitting to be consistent with local area Estimated Resident Populations and national estimates by sexual identity. We find that the geography of Australia’s sexual minority population is highly concentrated, with the highest proportions of the population identifying as a sexual minority in the inner areas of Australia’s largest cities. However, almost all parts of the county are home to at least a small sexual minority population, even in remote areas. While our estimates remain approximate due to data limitations, they provide a reasonable set of statistics on local area populations by sexual identity.
Applied Spatial Analysis and Policy